Comparative Study of Microwave Induced and Conventional Synthesis of Acetylated Sugar Isothiocyanates and Related Thiocarbamides - Atul V. Yadgire; Gajanan V. Korpe; Shirish P. Deshmukh (E-Journal of Chemistry)
The synthesis of several acetylated sugar isothiocyanates have been carried out under microwave irradiation in excellent yields of products by using related bromides and lead thiocyanate in sodium dried xylene. Several acetylated sugar thiocarbamides have been synthesized by the interaction of respective acetylated sugar isothiocyanates with appropriate aryl amines under microwave irradiation.